Implementasi Game Educaplay untuk Meningkatkan Hasil Belajar Peserta Didik pada Materi Keragaman Budaya Indonesiaku di Kelas 5 SDN Banjaran 4 - Pungky Selvia Taurista; Lusi Noviana Dewi; Alifvia Novita Putri Romadhoni; Mirza Sheila Sofiana; Dzulhijatul Awalin Zuroida; Anik Puji Rahayu; Nurita Primasatya (Universitas Nusantara PGRI Kediri, 2024)
This study aims to implement educaplay as an educational game used as a learning medium to improve students' learning outcomes on the topic